1992
DOI: 10.1055/s-2006-961543
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Three Compounds Extracted fromMorinda lucidaonPlasmodium falciparum

Abstract: The effects of three compounds, digitolutein (1), rubiadin 1-methyl ether (2) and damnacanthal (3) extracted from the stem bark and the roots of Morinda lucida Benth. on the growth of Plasmodium falciparum in vitro were investigated. The number of parasites (schizonts) decreased significantly in a dose-dependent manner, and 100% of inhibition was obtained with 30 to 40 micrograms of each compound tested. The IC50 values were calculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 1 publication
2
61
0
4
Order By: Relevance
“…Adanya pemberian tanaman obat tersebut terbukti dapat memperpanjang umur mencit yang terserang malaria dengan mencegah kerusakan pada hati dan limpa. Sudarsono et al, (2002) Koumaglo et al, (1992) dalam Sudarsono et al, (2002) menyatakan bahwa tiga komponen dari ekstrak kulit batang dan kulit akar, yaitu digitolurein, rubiadin-1-metil, dan damnakantal terbukti menghambat pertumbuhan P. falciparum secara in vitro. Selain itu pada P. berghei juga telah dilakukan penelitian, yaitu oleh Obih et al, (1985) menggunakan M. lucida sebagai penghambat pertumbuhan dari P. berghei.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Adanya pemberian tanaman obat tersebut terbukti dapat memperpanjang umur mencit yang terserang malaria dengan mencegah kerusakan pada hati dan limpa. Sudarsono et al, (2002) Koumaglo et al, (1992) dalam Sudarsono et al, (2002) menyatakan bahwa tiga komponen dari ekstrak kulit batang dan kulit akar, yaitu digitolurein, rubiadin-1-metil, dan damnakantal terbukti menghambat pertumbuhan P. falciparum secara in vitro. Selain itu pada P. berghei juga telah dilakukan penelitian, yaitu oleh Obih et al, (1985) menggunakan M. lucida sebagai penghambat pertumbuhan dari P. berghei.…”
Section: Pendahuluanunclassified
“…Bahan aktif yang sering ditemukan pada buah M. citrifolia adalah: L-arginine (Solomon, 1998), xeronine (Wang et al, 2002), senyawa polisakarida (Hirazumi dan Furusawa, 1999), damnakantal (Koumaglo et al 1992) dan antrakuinon. Senyawasenyawa ini antara lain berfungsi sebagai antiviral, sitotoksik, dan antimikrobia (Ali et al, 2000).…”
Section: Pendahuluanunclassified
“…(Rubiacae) is used in herbal decoctions in the treatment of "fevers" Sittie et al (1999), Lemmich et al (1999), malaria Watt (1962); Beyer-Bradwijk (1962) and diabetes Ettarh and Emeka (2004) in Africa. It has been reported that the main compounds that have useful antimalarial activities, which can be extracted from the stem bark and root of M lucida Benth are anthraquinones, digitolutein, rubiadin 1-methyl ether and damnacanthal Sittie et al (1999); Lemmich et al (1999); Koumaglo et al (1992). It has been shown that anthraquinones also have antibacterial properties (Koumaglo et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the main compounds that have useful antimalarial activities, which can be extracted from the stem bark and root of M lucida Benth are anthraquinones, digitolutein, rubiadin 1-methyl ether and damnacanthal Sittie et al (1999); Lemmich et al (1999); Koumaglo et al (1992). It has been shown that anthraquinones also have antibacterial properties (Koumaglo et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…A decoction of leaves and stems is used as a vermifuge (Williams, 2002). Scientific studies show that the anthraquinones of the Rubiaceae family exhibit some interesting in vivo biological activities, such as antimicrobial (Sittie et al, 1999), antifungal (Rath et al, 1995), hypotensive, analgesic (Younos et al, 1990), antimalarial (Adwankar and Chitnis, 1982;Koumaglo et al, 1992), antioxidant (Tripathi et al, 1997), antileukemic and mutagenic functions (Chang et al, 1995;Ismail et al, 1997). Apart from its medicinal value, this plant has also been used as natural food colorants and as natural hair dye (Samatha et al, 1996).…”
Section: Introductionmentioning
confidence: 99%